2019
DOI: 10.1161/strokeaha.118.024646
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Endovascular Therapy in Patients With Large Ischemic Core

Abstract: Background and Purpose— Endovascular therapy (EVT) is strongly recommended for acute cerebral large vessel occlusion with the Alberta Stroke Program Early CT Score (ASPECTS) ≥6 due to occlusion of the internal carotid artery or M1 segment of the middle cerebral artery. However, the effect of EVT for patients who have ischemic core with ASPECTS ≤5 (0–5) was not established. The purpose of this study was to elucidate the outcomes of EVT for patients with large ischemic core. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…All were observational studies utilizing prospectively collected stroke registry data. Apart from the study by Kakita et al, 25 all the included studies were retrospective. Four of the nine studies compared low ASPECTS patients undergoing EVT and best medical therapy.…”
Section: Characteristics Of Studies and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…All were observational studies utilizing prospectively collected stroke registry data. Apart from the study by Kakita et al, 25 all the included studies were retrospective. Four of the nine studies compared low ASPECTS patients undergoing EVT and best medical therapy.…”
Section: Characteristics Of Studies and Patientsmentioning
confidence: 99%
“…Both groups are similar in all baseline characteristics, except for more females in the best medical therapy group (49.3% vs 41.8%, p = 0.047) and more diabetic patients in the best medical therapy group (37.3% vs 17.7%, p = 0.007). Of the four studies that indicated the median ASPECTS, two studies 25,34 had significantly lower ASPECTS in the best medical therapy group (ASPECTS 3) compared to the EVT group (ASPECTS 5). There were more distal middle cerebral artery (M2 segment) occlusions in the best medical therapy group compared to the EVT group (15.4% vs 5.4%, p = 0.04).…”
Section: Characteristics Of Studies and Patientsmentioning
confidence: 99%
“…HERMES, as well as other studies that suggested a benefit of MT in low ASPECTS cohorts, treated patients based on heterogeneous imaging protocols with evidence suggesting that the positive results were driven by magnetic resonance imaging selection [1,4,5,13]. Since CT is by far the most common modality to select patients for MT in the real-world setting, concern was raised that these findings might not be applicable with CT-based selection [14].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from randomized clinical trials supporting the benefit of mechanical thrombectomy (MT) in patients presenting with large ischaemic cores on admission [Alberta Stroke Program Early Computed Tomography Score (ASPECTS) ≤ 5] is not yet available. Currently, the best available evidence is derived from retrospective studies, which are suggestive of a possible treatment effect, as well as procedural safety [1][2][3][4][5][6]. Pivotal thrombectomy studies have demonstrated the association of recanalization with outcome showing that, in cases of failed MT, only~20% of patients reach functional independence [7].…”
Section: Introductionmentioning
confidence: 99%
“…Current guidelines note reservations regarding the benefits from thrombectomy for a subgroup of patients with Alberta Stroke Program Early Computed Tomography Score (ASPECTS) <6 since they were mostly excluded from recent randomized trials 2–7. Nonetheless, evidence from the HERMES study and retrospective multicentric studies supports the benefit of mechanical thrombectomy (MT) for this population whose prognosis would be otherwise dismal 8–15. Successful recanalization and baseline ischemic lesion volume measured by either ASPECTS score or volumetrically have consistently been reported as independent predictors of outcome, along with other factors such as age 9–12.…”
Section: Introductionmentioning
confidence: 99%